P165 The reliability and performance of electronic monitors of inhaler use in a real world asthma clinical trial. (14th November 2013) - Patel, M; Pilcher, J; Shaw, D; Weatherall, M; Beasley, R
Abstract : Introduction: Electronic monitoring is one method to measure the use of inhaled therapy in asthma patients in clinical trials, though the reliability of these devices has been variable. Implementation of trial quality control processes and reporting on the performance of electronic monitors during patient use may help to better understand their utility and limitations. The Smartinhaler Tracker is an electronic monitor for metered dose inhalers (MDIs) that records the date, time and number of actuations to the nearest second. Objectives: In a recently completed 24-week real-world randomised controlled trial of 303 asthma patients at risk of severe exacerbations, Smartinhaler Tracker electronic monitors were used to measure actual use of budesonide/formoterol and salbutamol MDI therapy with two treatment regimens. Our aim is to report on the performance of these monitors, based on the implementation of extensive pre-trial and within-trial validation protocols for their use. Methods: Pre-study use checks involved two actuations of the MDI, with a further two actuations performed at least two hours later. Within-study monitor checks, performed prior to dispensing at follow-up clinic visits, included a computerised check of monitor clock function, actuation accuracy and battery life. Within-study data checks, performed after use of MDIs by participants during the trial, involved computerised checks of monitor clock function prior to data upload. Results: 2678/2728 (98.2%) monitors passed pre-study use checks; 46/50 monitors failed pre-study checks either because they did not record actuations that were performed, or erroneously recorded extra actuations. 76/2642 (2.9%) monitors dispensed to participants failed within-study monitor checks; 33/76 monitors failed because the battery was not fully charged. 51/2642 (1.9%) monitors failed data upload checks, mostly as a result of fluid immersion during participant use. 93/2642 (3.5%) monitors were lost or thrown away by participants. Complete data was available from 2498/2642 (94.5%) of dispensed monitors and 2498/2549 (98.0%) of returned monitors. Conclusions: The Smartinhaler Tracker is a reliable monitor for measuring MDI use in a real-world asthma clinical trial. Implementation of extensive monitor and data-checking protocols reduces data loss. The use of validated and reliable electronic monitors is the optimal method to assess patterns of inhaled medication use.